Enhanced Recovery After Cesarean Surgery (ERACS) Method Accelerates Mobilization and Duration of Hospitalization After Cesarean Section - Alfina Galuh Hannie Sisdayani; Erfan Efendi; Muhamad Hasan (Faculty of Medicine, Universitas Jember, 2024)
ERACS is a caesarean section method that supports recovery more quickly. The principle of ERACS is the use of multidrug anesthesia, namely bupivacaine at a reduced dose (<10 mg) and combined with fentanyl and morphine to maintain the quality of anesthesia so that patients can mobilize more quickly with minimal pain and reduce the duration of hospitalization. This research used an observational analytical design with a cross sectional approach in September – November 2023 at the Bina Sehat Jember Hospital. This study used 100 samples medical records with sampling using a purposive sampling technique and calculating using Slovin formula. The data was analyzed using Mann-Whitney test with a confidence level of 95%. The research results showed that the average walking mobility ability after ERACS was 10,10 hours, while conventional was 14.76 hours and the duration of hospitalization after ERACS was 2.22 days, while after conventional was 2.98 days. This is supported by the results of statistical tests which show that the significance value (p) for both variables is 0.000 (p < 0.05), which means there is a significant difference between the speed of walking mobilization and the duration of hospitalization with the SC method used. The conclusion of this study was that ERACS can speed up the ability to mobilize after surgery by up to 4.66 hours and the duration of hospitalization is 0.76 days shorter than conventional. Keywords: ERACS, mobilization, duration of hospitalization